THE EFFECTS OF PERSONALITY, REMUNERATION AND THE WORKPLACE TO WORK OBEDIENCE THROUGH WORK SPIRIT AS AN INTERVENTION STUDY OF INDONESIAN SHARIA BANKS IN DEMAK REGENCY - Aditya Angger Wibowo (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
This study uses two endogenous variables (morale and work compliance) and three exogenous variables (personality, remuneration, and workplace) to see how personality, remuneration, and workplace affect work compliance. Data for this study was collected through the questionnaire method. In addition, purposive random sampling method was used to collect a sample of 107 respondents. Structural Equation Model, operated by AMOS program, was used to analyse the data. The results showed that personality has a positive and significant impact on work obedience in Bank Syariah Indonesia Demak Regency; remuneration has a positive and significant impact on work obedience in Bank Syariah Indonesia Demak Regency; workplace has a positive and significant impact on work obedience in Bank Syariah Indonesia Demak Regency; and personality has a positive and significant impact on morale in Bank Syariah Indonesia Demak Regency. Work morale has not influenced work obedience at Bank Syariah Indonesia Demak Regency. Work enthusiasm has not yet influenced remuneration and workplace on work obedience at Bank Syariah Indonesia Demak Regency.